Pengaruh Komite Audit, Profitabilitas, dan Karakteristik Auditor terhadap Audit Report Lag pada Perusahaan Sektor Energi - Zahra, Yasmin Putri; Handayani, Dian Fitria (Jurnal Eksplorasi Akuntansi, 2025)
The purpose of this study was to analyze the effect of the Audit Committee, Profitability, and Auditor Characteristics on Audit report lag. The data used in this study are the annual reports of energy companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The data sampling method uses purposive sampling method based on certain criteria. Based on this method, a sample of 92 companies was obtained. Hypothesis testing in this study using multiple linear analysis. The results showed that KAP reputation had an effect on audit report lag, while audit committee, profitability, and audit tenure had no effect on audit report lag.